It takes team effort : men and women working together to enhance children's lives - Watson, Lemuel W. (Emerald Publishing Limited : IAP - Information Age Publishing, 2014)
This book explores the many ways and opportunities in which men and women might work together to highlight creative ways as well as examine the role of men in schools, families, and community engagement. The book helps to broaden the group's "collective identity" of those who work with male teachers and caregivers by expanding an understanding of their experiences in order to better ways of collaboration. This book serves as a practical guide and resource to challenge the status quo in following our own intuition about our life's work as men and women in early childhood education.The central theme that is sought here is to remember the general purpose of education: to enlighten for multiple purposes and to ask the resounding questions of how do we best achieve this purpose as men and women working together without the confines of gender roles, especially as educators in early childhood and the general educational setting where gender roles are specific to men and women's perceived ways of caring, nurturing, providing, and educating future generations.